PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOTITION (CIRC) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VI SEKOLAH DASAR - Zedderita, Hellena; Junaidi; Yumiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the fact that there are still students who are not able to solve basic mathematical problems and students answer questions carelessly, this is because some students do not understand the meaning of the question instructions. Therefore, the researcher applied the Cooperative Integrated Reading And Compotition (CIRC) cooperative learning model. The characteristics of the CIRC learning model can be seen from the types of questions presented, where in this model questions are presented in the form of story problems. Therefore, the purpose of this study was to determine the comparison of the Cooperative Integrated Reading and Compotition (CIRC) model to the critical thinking and mathematical problem solving skills of elementary school students. This study uses a quasi-experimental design form used in this study is nonequivalent control group design. From the analysis of data and hypotheses, it was concluded that the ability of both critical thinking and problem solving of Elementary School Students 3 Kampung using the Cooperative Integrated Reading and Compotition (CIRC) learning model is better than students who are taught using conventional learning models (lectures).